Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

Garçon manqué - Bouraoui, Nina (Le livre de poche, 2000)
Dans les années 70, la guerre d'Algérie est encore dans tous les esprits. Ce récit autobiographique décrit la difficulté de vivre en Algérie avec une mère française, et de vivre en France avec un père algérien
Keywords: 1900-1999; 1970-1979; afrique; afrique du nord; algérie; approches et analyses; arts; cours; discipline; europe; france; lit2815; premier cycle; périodes historiques; racisme; roman; régions géographiques; système colonial; systèmes d'oppressions; études littéraires

Amazons of the avant-garde: Alexandra Exter ... [et al.] - Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin.; Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin. (Solomon R. Guggenheim Museum, 2000)
Amazons of the Avant-Garde presents work by six Russian women who contributed to the development of modern art in the first quarter of the 20th century: Alexandra Exter, Natalia Goncharova, Liubov Popova, Olga Rozanova, Varvara Stepanova, and Nadezhda Udaltsova. The catalogue includes several essays that discuss the hindrances and influences affecting women in Russian avant-garde art circles. In addition, each artist featured in the exhibition is individually discussed at length, along with biographical timelines and excerpts of their writings from letters and publications. Color reproductions of the works in the exhibition accompany the essays to form a cohesive illustration of the art world in Russia during the first decades of the 20th century and the women who changed the aesthetic canons of their time. Alexandra Exter -- Natalia Goncharova -- Liubov Popova -- Olga Rozanova -- Varvara Stepanova -- Nadezhda Udaltsova
Keywords: 1900-1999; 1910-1919; 1920-1929; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; russie; régions géographiques; thématiques

Femmes & art au XXe siècle: le temps des défis - Dumas, Marie-Hélène (Hors-série, 1621-2606, 2000)
Que cela soit dans les plus prestigieuses expositions ou bien dans les livres consacrés à l'art, le très faible nombre de femmes représentées ou citées - en tous les cas en France - laisse perplexe. Pourtant, les femmes ont toutes les qualités pour être reconnues comme de grands artistés. Le débat autour du statut de la <> demeure donc plus que jamais d'actualité. Cet ouvrage pose la question de la reconnaissance des femmes dans le milieu artistique tout au long du XXe siècle. Par une mise en perspective historique - car l'art n'est pas en dehors de la société - il analyse comment les femmes ont participé à la création et au développement de différents mouvements (constructivisme, dadaïsme, surréalisme, art féministe. Fluxus, ou encore le cyber-art). Il permet également de mieux comprendre les démarches d'un grand nombre d'artistes, certaines très connues comme ou Yoko Ono ou Sophie Calle, ou ne devant surtout pas être oubliées comme Hannah Höch, ou Natalia Gontcharova. Ce livre vous invite à découvrir la richesse créatrice dont ont témoigné de nombreuses femmes de tous pays tout au long du XXe siècle, mais qui demeure trop souvent invisible.
Keywords: 1900-1999; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sciences humaines; sex1911; thématiques

L'événement - Ernaux, Annie (NRF, 2000)
L'occasion d'un banal examen dans un cabinet médical replonge la narratrice plus de trente ans en arrière, en janvier 1964, au moment de son avortement clandestin.
Keywords: 1900-1999; arts; autobiographie; avortement; cours; discipline; europe; france; justice reproductive; lit2815; lit3220; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires

Coming Out of the Castle: Gothic, Sexuality and the Limits of Language - Grove, Allen W. (Historical Reflections / Réflexions Historiques, 2000)
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; histoire; histoire et politique; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; thématiques; études littéraires